1998
DOI: 10.1007/s004670050527
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelium and nitric oxide in childhood hypertension

Abstract: Vascular endothelium releases nitric oxide (NO), an important vasodilator that is continuously synthesised by the constitutive enzyme, endothelial nitric oxide synthase (NOS). This maintains a constant vasodilator tone which is diminished in adult hypertension, due to reduced endothelium-dependent vascular relaxation, which is NO dependent. In childhood, however, hypertension is often secondary, and normalisation of blood pressure by removal of cause (e.g. renal artery stenosis, catecholamine-producing tumour)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 200 publications
(157 reference statements)
0
12
1
Order By: Relevance
“…Indeed, studies have shown that reduced NO availability 45 and increased endothelial derived constrictor factors 44 secondary to endothelial dysfunction or raised endogenous inhibitors of NO synthase play a role in the pathogenesis of hypertension even in children. 46 Carotid intima-media thickness is a well-established, independent predictor of future cardiovascular risk in asymptomatic adults. In a meta-analysis, Lorenz et al 47 reported that an absolute difference in intima-media thickness of 0.1 mm was associated with a relative risk of myocardial infarction and stroke of 1.15 and 1.18, respectively, in adults over the age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that reduced NO availability 45 and increased endothelial derived constrictor factors 44 secondary to endothelial dysfunction or raised endogenous inhibitors of NO synthase play a role in the pathogenesis of hypertension even in children. 46 Carotid intima-media thickness is a well-established, independent predictor of future cardiovascular risk in asymptomatic adults. In a meta-analysis, Lorenz et al 47 reported that an absolute difference in intima-media thickness of 0.1 mm was associated with a relative risk of myocardial infarction and stroke of 1.15 and 1.18, respectively, in adults over the age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the numerous observational and epidemiological studies proving the prognostic significance of IMT in hypertension and a marker of atherosclerosis, there are some uncertainties regarding the pathophysiological background of the increased intimamedia thickness. Recently, the role of nitric oxideendothelin-1 imbalance has been demonstrated as one of the leading pathophysiologic factors determining essential hypertension [18][19][20] and there are also observations available pointing out the possible role of the NO/ endothelin imbalance in determination of intima-media thickness among hypertensives [21,22]. As the majority of the previous studies assessed the relationship of NO/ endothelin imbalance with intima-media thickness mainly in adult essential hypertensives, in the present study we wanted to test whether such a correlation exists between these endothelial factors and intima-media thickness of the carotid arteries already in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite a number of epidemiologic data, 2,3,4,5 there are only a few reports about the physiopathologic mechanisms involved in childhood hypertension. 6,7 Experimental models of hypertension and the efficacy of angiotensin converting enzyme (ACE) inhibition as treatment indicate that the renin angiotensin system (RAS) is probably involved in many hypertensive states. 6 Classically, the RAS is considered a peptidergic hormone system in which precursor peptides are transformed into active products through a stepwise enzymatic processing assumed to sequentially convert angiotensinogen into angiotensin II (Ang II).…”
mentioning
confidence: 99%
“…8,9 Among these putative RAS mediators, angiotensin-(1-7) [Ang- (1)(2)(3)(4)(5)(6)(7)] is particularly interesting because it can be formed directly from angiotensin I (Ang I) by neutral-endopepdidase (NEP) 24.11 or prolyl-endopeptidase (PEP), or from Ang II via PEP, prolyl carboxypeptidase, 8,9 or the enzyme ACE2, a homolog of ACE in humans, mice, and rats. 10 A growing body of evidence suggests that Ang- (1)(2)(3)(4)(5)(6)(7) participates in the control of hydroelectrolyte balance 11,12 and plays a counterregulatory role within the RAS. 8,13 Ang-(1-7) generally opposes the vascular and proliferative effects of Ang II 8,13,14 and exerts complex renal actions.…”
mentioning
confidence: 99%